(untitled) (National Administration Journal, 2024)
Over the last five years, three emblematic Free Trade Agreements (FTAs) marked their tenth anniversary: the Dominican Republic-Central America-United States FTA, the agreement with China and the Association Agreement with the European Union. The importance of the comparative evaluation of the performance of these FTAs as benchmarks in Costa Rican trade policy is discussed. For each of these agreements, different multidimensional impacts in both trade and non-trade areas are assessed. Trade results are analyzed in quantitative terms of exports, imports, trade balance, diversification of the exportable supply and foreign direct investment. But, also, for each of these agreements, non-trade components of enormous importance are studied, reflected in unprecedented results, such as the breaking of state monopolies, as was the case of the FTA with the United States. This study focuses on the evaluation of the specific impacts of each agreement, with the objective of providing an original analysis of results that are presented as discordant and asymmetrical.